Antioxidant capacities and in vitro anti-microbial activities of rice (Oryza sativa var Bajong) from Borneo - Lam, Xiu Qian; Khong, Heng Yen; Tay, Siow Phing; Isabel Lim, Fong (Springer, 2025)
Rice contains antioxidants and phenolic components that exert anti-infammatory and anticancer properties. Different geographical areas produce rice with various chemical constituents and phytochemicals, in turn these confer diferential protective efects including antimicrobial and anticancer properties. Sarawak rice, Oryza sativa var Bajong (Bajong), a fragrant dark purple rice grain harvested from two locations in Sarawak, namely interior Lubok Nibong (LN) and coastal Sri Aman (SA), was assessed for their antioxidant properties and antimicrobial activities. The rice was extracted using methanol solvent and evaluated for total phenolic content (TPC), total favonoid contents (TFC), as well as their antioxidant and antimicrobial activities based on the Folin–Ciocalteu assay, the aluminium calorimetric method, 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and disk difusion assay, respectively. Using dual-wavelength measurement, Bajong LN showed 2.16% higher amylose content than Bajong SA. Furthermore, 24-h extract of Bajong LN and 48-h extract of Bajong SA exhibited high antioxidant properties (34–70 µg/mL) and were rich in phenolic (46.54±2.62 mg GAE/g; 25.28±3.91 mg GAE/g) and favonoid contents (5.53±0.36 mg QCE/g; 7.7±2.19 mg QCE/g) respectively. It is interesting to note that 72-h Bajong extract exhibited the largest zone of inhibition (9–9.3 mm) against Gram-negative Pseudomonas aeruginosa (Ps. aeruginosa), which correlated to the high TPC and TFC despite a reduction of antioxidant activity due to prolonged extraction hours. These signifcant results conferred added value to a staple, health-promoting Bajong had warranted it to be further investigated as a nutraceutical and pharmaceutical crop.